Open versus closed surgical exposure of canine teeth that are displaced in the roof of the mouth - Parkin, Nicola (Cochrane Database Syst Rev, 2017)
BACKGROUND: Palatally displaced canines or PDCs are upper permanent canines, commonly known as 'eye' teeth, that are displaced in the roof of the mouth. This can leave unsightly gaps, cause damage to the surrounding roots (which can be so severe that neighbouring teeth are lost or have to be removed) and, occasionally, result in the development of cysts. PDCs are a frequent dental anomaly, present in 2% to 3% of young people. Management of this problem is both time consuming and expensive. It involves surgical exposure (uncovering) followed by fixed braces for two to three years to bring the canine into alignment within the dental arch. Two techniques for exposing palatal canines are routinely used in the UK: the closed technique and the open technique. The closed technique involves uncovering the canine, attaching an eyelet and gold chain and then suturing the palatal mucosa back over the tooth. The tooth is then moved into position covered by the palatal mucosa. The open technique involves uncovering the canine tooth and removing the overlying palatal tissue to leave it uncovered. The orthodontist can then see the crown of the canine to align it. OBJECTIVES: To assess the effects of using either an open or closed surgical method to expose canines that have become displaced in the roof of the mouth, in terms of success and other clinical and patient‐reported outcomes. SEARCH METHODS: Cochrane Oral Health’s Information Specialist searched the following databases: Cochrane Oral Health’s Trials Register (to 24 February 2017), the Cochrane Central Register of Controlled Trials (CENTRAL) (in the Cochrane Library, 2017, Issue 1), MEDLINE Ovid (1946 to 24 February 2017), and Embase Ovid (1980 to 24 February 2017). The US National Institutes of Health Ongoing Trials Register (ClinicalTrials.gov) and the World Health Organization International Clinical Trials Registry Platform were searched for ongoing trials. No restrictions were placed on the language or date of publication when searching the electronic databases. SELECTION CRITERIA: We included randomised and quasi‐randomised controlled trials assessing young people receiving surgical treatment to correct upper PDCs. There was no restriction on age, presenting malocclusion or type of active orthodontic treatment undertaken. We included unilaterally and bilaterally displaced canines. DATA COLLECTION AND ANALYSIS: Two review authors independently screened the results of the electronic searches, extracted data and assessed the risk of bias in the included studies. We attempted to contact study authors for missing data or clarification where feasible. We followed statistical guidelines from the Cochrane Handbook for Systematic Reviews of Interventions for data synthesis. MAIN RESULTS: We included three studies, involving 146 participants. Two studies were assessed as being at high risk of bias. The main finding of the review was that the two techniques may be equally successful at exposing PDCs (risk ratio (RR) 0.99, 95% confidence interval (CI) 0.93 to 1.06; three studies, 141 participants analysed, low‐quality evidence). One surgical failure was due to detachment of the gold chain (closed group). One study reported on complications following surgery and found two in the closed group: a post‐operative infection requiring antibiotics and pain during alignment of the canine as the gold chain penetrated through the gum tissue of the palate. We were unable to pool data for dental aesthetics, patient‐reported pain and discomfort, periodontal health and treatment time; however, individual studies did not find any differences between the surgical techniques (low‐ to very low‐quality evidence). AUTHORS' CONCLUSIONS: Currently, the evidence suggests that neither the open or closed surgical technique for exposing palatally displaced maxillary canine teeth is superior for any of the outcomes included in this review; however, we considered the evidence to be low quality, with two of the three included studies being at high risk of bias. This suggests the need for more high‐quality studies. Three ongoing clinical trials have been identified and it is hoped that these will produce data that can be pooled to increase the degree of certainty in these findings.